ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN RUMAH TANGGA PETANI NANAS DI DESA ASTOMULYO KECAMATAN PUNGGUR KABUPATEN LAMPUNG TENGAH - Aurora, Ferentia; Haryono, Dwi; Marlina, Lina (Jurnal Ilmu-Ilmu Agribisnis, 2020)
This research aims to analyze pineapple farming income, household income, and the prosperity grade of pineapple farmer?s household in Astomulyo Village. This research was purposively conducted in February-March 2019 at Astomulyo Village, Punggur Sub District, Central Lampung Regency by survey method. There are 63 respondents taken by Simple Random Sampling. The data was analyzed quantitative and qualitative by farming income method (R/C ratio), household income based on the criteria of BPS (2016), and the welfare level of farmer?s household based on the criteria of BPS (2014). The results showed that average income of pineapple farmers based on cash cost and total cost per hectare wasRp46.526.933,00/year and Rp29.502.072,00/year. Pineapple farming was beneficial because it gained acceptance ratio with cash cost and total cost more than one (R/C ratio) as 3.33 and 1.80. The household income of pineapple farmers was categorized as high income for it reached Rp4.000.000,00/month until Rp6.000.000,00/month. The most contributed income was derived from pineapple farming activities (66.49%), the others were from off farming (13.74%), non-pineapple on farming (12.39%), and nonfarming activities (7.37%). Based on BPS criteria, 50.79% pineapple farmers household in Astomulyo Village were categorized in not prosperous and 49.21% as prosperous farmers household.Key words: household income, pineapple, prosperity grade